A Tetrahydroxycalix[4]arene Derivative with All Bridges Monosubstituted with Methoxy Groups - Itzhak, Norbert; Biali, Silvio E. (Synthesis, 2015)
Reduction of the carbonyl groups of tetrahydroxyketocalix[4]arene with NaBH4 in propan-2-ol, followed by heating the product to reflux in MeOH–H2SO4, yields a mixture of stereoisomers of the tetrahydroxycalix[4]arene derivative with all bridges monosubstituted by a methoxy group. To structurally characterize the compound, the mixture of isomers was derivatized by reaction with di-tert-butyl dicarbonate–DMAP. X-ray crystal structure analysis of the all-cis isomer of the product (obtained by fractional crystallization), corroborates the presence of Boc protecting groups at the lower rim (and thus underivatized OH groups in the starting material), and four methoxy groups at the bridges.
Keywords: calixarenes; reduction; protecting group; phenols; carbocation